Prove that tanA + tanB/cotA + cot B = tan A tan B
Answers
Answer:
Since cotA = 1/tanA, substituting to get everything in terms of tanA and tanB, then (tanA + tanB)(1 - cotAcotB) = (tanA + tanB)(1 - 1/(tanAtanB) =
((tanA + tanB)(tanAtanB - 1))/(tanAtanB) - (i)
(cotA + cotB)(1 - tanAtanB) = (1/tanA + 1/tanB)(1 - tanAtanB) =
((tanA + tanB)(1 - tanAtanB))/(tanAtanB) - (ii)
Adding (i) + (ii) you get 0, since (i) = - (ii)
Answer:
First, chose one of the variables to isolate.
In this case, let’s isolate x . In order to do so, we need to cancel out the y variable. Multiply the first equation by 2 and the second by 3 to get the following:
4x−6y=22
15x+6y=54
Now adding both equations would rid us of the y variable to get:
19x=76 hence x=4
Now replace x by 4 in any of the original equations:
5(4)+2y=18
20+2y=18
2y=−2
y=−1
So the answer to the equations is 4;−1